Improving IT Service Management in Customer Service Business: A Case Study - Žilinskienė, Inga; Norkus, Justinas (Information & Media, 2022)
Organisations that provide information technology services mostly set goals for improving the quality and management of services. The ability to remain competitive is one of the most critical factors in any modern organisation’s success. For business processes to be successful, it is necessary to rely on rational and well-thought-out solutions. In many cases, data-based solutions create conditions to avoid or reduce significant risks. The article examines the possibilities of applying IT processes to improve customer service and presents its improvement outcomes. Customer satisfaction with the services provided is directly correlated with the quality of services. The research investigates and empirically evaluates the existing IT incident management processes of the selected company and provides opportunities for their improvement. After analysing incident management processes in the selected company, an improvement of the incident management processes was presented to eliminate the identified deficiencies. Descriptive and inferential statistical methods were used to evaluate the effectiveness of the improvements. The results obtained show that the improved process had a statistically significant positive impact on improving the customer service quality. Therefore, it can be stated that the implemented changes are effective and useful in the context of the company’s operations.